Analisis Kelimpahan Ikan Karang di Fish Shelter dan Terumbu Karang Alami Perairan Karang Melantut Pantai Rebo Kecamatan Sungailiat, Kabupaten Bangka - Edwin Andrian; Sudirman Adibrata; Suci Puspita Sari (Universitas Bangka Belitung, 2020)
The potential of these mineral resources has caused mining activities in the rebo coast waters. Tin mining activities at sea cause problems for coral reef ecosystems and other marine biota. Efforts to overcome these problems include rehabilitation of ecosystems such as coral reef transplants and the creation and sinking of Fish Shelter in Rebo Coastal Waters. This study aims to determine the number of species and abundance of reef fishes in the Fish Shelter location and in the Natural Coral Reef of the Coral Waters of Rebo Beach and to analyze the comparison of coral fish abundance in the two locations. Data collection was carried out by the Belt Transect and Visual Census methods, while the coral reef data collection was carried out by the Line Intersept Transect (LIT) method. The results showed an abundance of reef fish at Station 1 on the Natural Coral Reef (NCR) consisting of 8 families and 16 species with a total of 110 individuals/ha and 10 families and 12 species with 125 individuals/ha at the Fish Shelter site. At station 2 the abundance of reef fish in the Natural Coral Reef (NCR) consists of 7 families and 12 species with a total of 120 individuals/ha and 10 families and 15 species with a total of 134 ind/ha at the Fish Shelter site. One way ANOVA test results at Station 1 comparisons of coral fish abundance at Fish Shelter and Natural Coral Reef locations with a significance value of 0.177, then H0 is accepted.